From #tahrir to #occupywallstreet: How Can Information Science Make Sense of Social Media and Protests? - Saleh, Nasser; Khashman, Nouf; Kamal, Ahmad (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
Panel: There has been a great attention towards the use of social media in/and revolutionary movements (more recently in the Arab world). This panel introduces some different frameworks that can be used in information science to study these phenomena along with a discussion with CAIS/ACSI members about possible research areas. Panel: Une grande attention a été portée à l’utilisation des médias sociaux dans/et les mouvements révolutionnaires (plus récemment dans le monde arabe). Ce panel introduit quelques différences dans les cadres pouvant être utilisés en sciences de l’information science pour étudier ces phénomènes. Suivra une discussion avec les membres de CAIS/ACSI des possibilités de recherches sur le sujet.